Impacts of a mind mapping-based contextual gaming approach on EFL students' writing performance, learning perceptions and generative uses in an English course. (August 2019) - Fu, Qing-Ke; Lin, Chi-Jen; Hwang, Gwo-Jen; Zhang, Lixin
Abstract: To situate students in authentic English learning and practicing contexts so as to facilitate their writing performance, in this study, a mind mapping-based contextual gaming approach was proposed. A quasi-experiment was implemented by recruiting two English tourism classes of students from a university of science and technology in northern Taiwan. One class was scheduled to learn with the proposed approach, and the other was arranged to learn with the conventional contextual gaming approach. The students' writing performance, learning perceptions and generative uses were measured to evaluate the effectiveness of the proposed approach. It was found that, compared to the control group students; the experimental group students who learned with the proposed learning approach had better writing performance in the aspects of fluency and elaboration with a small effect size. Additionally, it was found that most students considered the game to be beneficial and interesting, and they were in favor of the mind mapping strategy. Moreover, it was also found that the proposed learning approach is more likely to help students produce positive thoughts and feelings, generate diverse ideas, create a sense of exoticism and express actions or intent of actions. Finally, the limitations of the study and some suggestions for improvement of this proposed gaming learning environment and approaches are provided. Highlights: A mind mapping-based contextual gaming approach was proposed. An experiment was conducted to evaluate the performance of the proposed approach. The approach has been applied to an English tourism course. The approach improved the students' writing performance and language use. Some suggestions for improvement of this proposed approach are provided.